Frequency of dihydropyrimidine dehydrogenase and UDP-glucuronosyltransferase 1A1 variants in cancer patients requiring chemotherapy: A single-center study in southern India - Kevin Nischay Gangavarapu; Nandini Shyamali Bora; Srinivas Maddali; Qurratulain Hasan (Golestan University Of Medical Sciences, 2023)
Abstract Background: Cancer treatment using drugs metabolized by the enzymes dihydropyrimidine dehydrogenase (DPYD) and UDP-glucuronosyltransferase 1A1 (UGT1A1) results in adverse effects for some patients. This is frequently reported in cancer patients undergoing therapy with 5-fluorouracil, capecitabine, and irinotecan who have polymorphisms in the genes coding for DPYD and UGT1A1. The present study assessed the DPYD*2A and UGT1A1*28 polymorphisms in cancer patients before starting chemotherapy to identify the individuals at risk of developing an adverse drug reaction. Methods: Genomic DNA was isolated from patients and subjected to PCR amplification using specific primers to study DPYD*2A and UGT1A1*28 polymorphisms. The PCR products were assessed by Sanger sequencing for establishing the genotype. Results: Of 75 cancer patients requiring treatment with drugs metabolized by DPYD and UGT1A1, 2 (2.66%) and 12 (29.27%) were likely to have adverse reactions based on DPYD*2A and UGT1A1*28 genotyping, respectively. Conclusion: Our findings indicate that carrying out genotyping for these two polymorphisms will help a large number of patients requiring treatment with 5-fluorouracil, irinotecan, and capecitabine.